STATISM, EMANCIPATION AND THE LEFT: UNDERSTANDING UNCONVENTIONAL POLITICAL PARTICIPATION IN COSTA RICA - Chavarría-Mora, Elías (Revista Latinoamericana de Opinión Pública, 2019)
Ideology has been traditionally considered to be an explanation of political behavior, both inside and outside academia, which has been nowadays mostly abandoned. This paper sets out to investigate if a relationship between ideology and unconventional political participation exists, for the Costa Rican elections of 2014. It yields results that indicate that while the majority of Costa Ricans do not engage in political participation, there is a minority that does, with an identifiable emancipatory, statist and leftist ideology. A strong contradiction is found in the population between their ideological self-identification and their values and attitudes. The paper then argues in favor of more nuanced measurements of ideology than self-identification questions. Furthermore, it becomes apparent that each form of participation has a different relationship with the ideological elements.Therefore, studying them as if they were one should be avoided.